(untitled) (Baghdad Science Journal, 2024)
In the present work, the electrical conductivity of chloramphenicol was measured in water and methanol at different temperature degrees 293-313 K. The parameters of conductivity equivalent conductance at infinite dilution ( Λ0), the association constant (KA) and distance parameter (R) were all recorded by using Lee-Wheaton equation and the thermodynamic parameters (ΔH, ΔG, and ΔS) were calculated as well. The behavior of a compound can be predicted through computational calculations; taking 2,2-dichloro-N-[(1R,2S)-1,3-dihydroxy-1-(4-nitrophenyl) propan-2-yl] acetamide, for example. There is an abundance of theoretical information available about how this compound behaves in different solvents, such as water and methanol. The secret lies in analyzing the compound’s HOMO and LUMO energies, which can be determined through advanced computational calculations using methods like AM1, PM3, and HF. The potential of the compound was different when changing the solvent and this is due to the value of energy and other theoretical factors like the molecular volume and Connolly parameters.